Greenhouse gas emission and rice production in Nigeria: An ARDL bounds testing approach (Journal of the Bangladesh Agricultural University, 2020)
Rice cultivation is attributed as a major agricultural greenhouse gas (GHG) emitter which contributes to rising global temperatures impacting agricultural productivity, environment and livelihood. However, studies on greenhouse gas emissions in rice production is still limited in many developing countries, including Nigeria. This paper examines the relationship between greenhouse gas emission and rice production in Nigeria using the Autoregressive Distributed Lag (ARDL) bounds test. Annual time series data of four selected variables rice output, rice yield, rice harvested area, fertilizer usage and greenhouse emission (CH4) in rice production was used over the period 1961 to 2017. Empirical results provide evidence of long run relationship between greenhouse gas emission and rice production in Nigeria. The result of the estimated elasticities of both the short run and long run analysis indicates that all the variables except fertilizer usage in the long run, significantly explain changes in greenhouse gas emission in rice production. The findings recommend the need to adopt new approaches to rice cultivation that will boost productivity using less energy and land resources in order to decrease GHG emissions. The use of improved seed varieties that will increase yield using less land area, fertilizer application, water usage and chemical in production could also be a good strategy of reducing GHG emissions in rice cultivation, which has an impact on atmospheric pollutions and global warming.J Bangladesh Agril Univ 18(2): 283–288, 2020https://doi.org/10.5455/JBAU.83883